Optimization for a Grid-connected Hybrid PV-wind-retired HEV Battery Microgrid System. (May 2017) - Li, Shuchun; Sun, Fengchun; He, Hongwen; Chen, Yong
Abstract: This paper presents a study on the retired EV(electrical vehicle) battery in hybrid PV-Wind-Retired Battery microgrid system. An optimal control theory based algorithm is proposed to determine the optimal application of the battery pack for a residential house equipped with a roof-top PV system and a wind turbine. The main goal of this algorithm is to low the cost of energy purchased from the main grid and maximize the profits for selling energy generated by photovoltaic arrays and wind turbine.